These ghosts are family : a novel - Card, Maisy (Simon & Schuster, 2020)
"These Ghosts are Family centers on Abel and Vera Paisley, a working-class Jamaican couple, striving to build a better life for their children. Abel travels to London in the early 1960s in search of fortune. Instead, he sees an opportunity to escape the drudgery of his life by faking his death and assuming a new identity. Vera, now a widow, is racked with guilt over her husband's "death" and takes out her grief on her children, Irene and Vincent. The effects of Abel's decision reverberate across generations. Ghosts follows the Paisleys over time and across continents, as they wrestle with the burdens of family lore and struggle to forge independent identities. Despite everything, Abel finds a second chance at love. Vincent follows his dream to move to New York. Irene also moves to New York but realizes you can never fully leave the past behind. Set in the United States and Jamaica, Card's debut incorporates elements of gothic fiction and Jamaican folklore to explore the immigrant experience, as told through the voices of these flawed, memorable characters. In luminous prose that announces the arrival of a new American talent, These Ghosts are Family inspects the weight of long-held secrets, the limits of forgiveness, and the complexities of family ties"--